2023
DOI: 10.1108/lodj-05-2022-0227
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive leadership and innovative work behaviors: a moderated mediation model

Abstract: PurposeThis research aimed to determine how and why inclusive leadership is effective in innovative work behaviors (IWBs). For this purpose, a conceptual model including inclusive leadership, IWBs, psychological resilience capacity and leader–member exchange (LMX) has been proposed.Design/methodology/approachTo test the proposed model, a questionnaire was administered to the employees of a Turkish telecommunications company located in Istanbul and Ankara. Data obtained from 459 employees selected by convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 51 publications
(131 reference statements)
1
34
0
4
Order By: Relevance
“…According to existing literature, supportive inclusive leadership is a robust predictor of each level related to IWB. Existing studies highlighting the literature show that inclusive leadership has a significant and positive relationship with IWB (Bataineh et al, 2022;Javed et al, 2018Javed et al, , 2020S€ ur€ uc€ u et al, 2023). So, the hypothesis is: H1.…”
Section: Inclusive Leadership and Innovative Work Behaviormentioning
confidence: 94%
See 3 more Smart Citations
“…According to existing literature, supportive inclusive leadership is a robust predictor of each level related to IWB. Existing studies highlighting the literature show that inclusive leadership has a significant and positive relationship with IWB (Bataineh et al, 2022;Javed et al, 2018Javed et al, , 2020S€ ur€ uc€ u et al, 2023). So, the hypothesis is: H1.…”
Section: Inclusive Leadership and Innovative Work Behaviormentioning
confidence: 94%
“…It does this by valuing and respecting individual diversity, developing a sense of community and creating an inclusive workplace. The organization and the dignity of the workplace promote innovative work practices (Javed et al, 2019;S€ ur€ uc€ u et al, 2023).…”
Section: Workplace Dignity As a Mediatormentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Prime and Salib (2014) conducted research on six countries and found that leaders' behaviors of courage, humility, empowerment and accountability influence increase inclusion at work. Inclusive leaders through their empowering behavior can involve others in decision-making and delegating powers (Sürücü et al ., 2023). Similarly, through humility, they help followers in admitting mistakes, accepting criticism and acknowledging others (Bao et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%